About enterprise credit in the innovation economy - Yu. V. Kuzminykh; T. V. Shmulevich (Путеводитель предпринимателя, 2020)
The article analyzes the existing foreign and domestic practice, approaches to the diagnosis of the creditworthiness of companies. It submitted a detailed study rated borrowers creditworthiness. Recommendations for improving credit scoring legal persons in the modern world.